RETRACTED: Managing electric motive power modes with regard to traction energy operation conditions - Tretyakov Evgeny; Denisov Ilya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001